1967
DOI: 10.1126/science.158.3797.135
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Transport: Inhibitory Factor in Sweat of Patients with Cystic Fibrosis

Abstract: A factor inhibitory to sodium transport exists in the sweat of patients with cystic fibrosis of the pancreas. When the duct system of the rat parotid was perfused with sweat from patients, marked inhibition of sodium reabsorption was observed. Perfusion with sweat from normal subjects caused no change in sodium reabsorption. The factor thus demonstrated may be responsible for the increased sodium concentrations in the sweat of patients with cystic fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1969
1969
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(26 citation statements)
references
References 5 publications
1
25
0
Order By: Relevance
“…Since the isolated factor has basic or cationic groups (20), it may be electrostatiscally bound to the heparin which is anionic. This effect has been observed for heparin and other polyanions when C F factors from sweat and saliva have been tested using the Mangos retrograde perfusion method (29,31) and is explicable on the basis of their postulated cationic character (13,30). The heparin effect is also consistent with the in vivo and in vitro findings of Doggett and Harrison (15,16) who used ca.…”
Section: T L M E I N M I N U T E Ssupporting
confidence: 79%
See 1 more Smart Citation
“…Since the isolated factor has basic or cationic groups (20), it may be electrostatiscally bound to the heparin which is anionic. This effect has been observed for heparin and other polyanions when C F factors from sweat and saliva have been tested using the Mangos retrograde perfusion method (29,31) and is explicable on the basis of their postulated cationic character (13,30). The heparin effect is also consistent with the in vivo and in vitro findings of Doggett and Harrison (15,16) who used ca.…”
Section: T L M E I N M I N U T E Ssupporting
confidence: 79%
“…These factors have in general been described as immunoglobulins, complement components, abnormal proteins, peptides ranging from 1,000-10,000 in molecular weight, as well as abnormal enzymes and polyamines and/or their metabolites (7, 8, 10-12, 15, 20, 22, 29, 31, 33,35). Various bioassays have been developed for the detection of these CF factors and include the oyster gill ciliary assay developed by Bowman et al (7) and modified by Schmoyer et al (39), a fresh water mussel assay by Besley et al (4), a modification of the original rabbit tracheal assay (40) described by Conover et al (9), the retrograde perfusion assay by Mangos (29)(30)(31), and its modification as described by Taylor et al (41), and recently a short-circuit current membrane system by Araki et al (1) adapted from Asano (2). In addition, a means of detection utilizing isoelectric focusing has been described by Wilson and Fudenberg (43).…”
Section: Speculationmentioning
confidence: 99%
“…The abnormal behavior of exocrine secretions has drawn attention to the mechanism of glycoprotein synthesis and secretion (4,9,11,15,16,18,21). Finally, the consistent alteration in the content of certain inorganic components of exocrine fluids has suggested the possibility of a defect in ion transport (12).…”
Section: Speculationmentioning
confidence: 99%
“…The concept is also consistent with the theory of HADORN et al [lo], who postulate that a secretin-type deficiency causes the inadequate fluid and electrolyte content of some secretions and the high salt content of sweat in CFP. Overactivity [l, 2,6,71 or dysfunction 1171 of the autonomic nervous system has been described, and other investigators have demonstrated an inhibitory factor in blood [19] and sweat [14] of patients with this disease. No attempt, however, has been made to reproduce CFP in an animal model by combining parasympathomimetic stimulation with cholinergic blockade.…”
Section: Discussionmentioning
confidence: 99%